A Minimal Design of a Human Infant Presence: A Case Study Toward Interactive Doll Therapy for Older Adults With Dementia - Sumioka, Hidenobu; Yamato, Nobuo; Shiomi, Masahiro; Ishiguro, Hiroshi (Frontiers in Robotics and AI, 2021)
We introduce a minimal design approach to achieve an infant-like robot for interactive doll therapy that provides emotional interactions for older people with dementia. Our approach stimulates their imaginations and then facilitates positive engagement with the robot by just expressing the most basic elements of human-like features. Based on this approach, we developed HIRO, a baby-sized robot with an abstract body representation and no facial features. The recorded voice of a real human infant emitted by robots enhances the robot's human likeness and facilitates positive interaction between older adults and the robot. A field study showed that HIRO was accepted by older adults with dementia and facilitated positive interaction by stimulating their imagination although we did not find any significant difference between HIRO and a infant-like robot with a smiling face. We also discuss the importance of a minimal design approach in elderly care during post-Covid-19 world.